THE EFFECTS OF ZINC OXIDE AND CLAY NANOPARTICLES ON THERMAL, BARRIER, AND MECHANICAL PROPERTIES OF POLYPROPYLENE AND HIGH DENSITY POLYETHYLENE - Atayev, Parahat; Bekat, Tugce; Oner, Mualla (YILDIZ TECHNICAL UNIV, 2015)
Rod-shaped ZnO crystals were synthesized by chemical precipitation method and added into polypropylene and high density polyethylene together with montmorillonite particles by melt extrusion method. Surface modification with stearic acid was applied to the ZnO particles. Decreased oxygen permeability and increased elastic modulus were observed for both polypropylene and polyethylene when ZnO and clay particles were added together. Thermal properties of the polymers were preserved with the addition of the particles.
Keywords: Polyolefins; barrier property; mechanical properties; ZnO; ANTIBACTERIAL PROPERTIES; Engineering